Realtime earthquake visualization and interactive analysis - Ye, Ruiyi (Nanyang Technological University, 2022)
Earthquakes pose a significant risk to the safety of our society and communities. With improved technology and measuring tools, earthquake data have become more accessible and grown in size. However, it is challenging to conduct an efficient earthquake analysis on those large amounts of data. To address this problem, this project proposes a web-based real time earthquake visualization tool, QuakeVisual, that offers users a more interactive way to analyse earthquakes. The QuakeVisual allows queries on earthquake timing, location, and magnitude and can visually display the results in a 2D map view with regular circle nodes and cluster form nodes. On top of that, it also provides an accelerated playback of the earthquake events feature which animates the earthquake points in time sequence. To evaluate the effectiveness of the various features provided by QuakeVisual, a user study was conducted. Results from the user study showed that features provided in QuakeVisual have increased the users’ querying speed for the earthquakes, and the playback of earthquake events has allowed users to gain more insights about the temporal patterns of earthquakes.